The Problem of Home Education of Schoolchildren in Pedagogical Theory and Practice - M. V. Romanova; Yu. A. Safronova (Открытое образование (Москва), 2023)
Purpose of the study. In modern society, the education system is undergoing global changes, both technical and methodological. What affects the organization of school education, the manifestation of social difficulties, such as overcrowded classes, lack of staff in schools, dif-ficulties for children to follow patterns in the learning process or program changes. More and more parents are transferring their children to home schooling. If a few years ago scientists con-sidered this direction of education as an alternative to public and private schools, now this direc-tion borders on the “mainstream” in educational practice both in Russia and abroad, especially in the USA, where it perhaps the fastest growing form of education (from 2% to 8% per year over the past few years). In different countries, various forms of home education, their own specifics and local laws regulate this format of education. In Russia, the Federal Law “On Education” of 1992 approved the choice for schoolchildren to study at school or outside its walls, and the Con-stitutional Court of the Russian Federation in 2000 guaranteed the availability of this form of education. It is envisaged to receive general education in full-time/part-time forms or extramural studies, as well as outside organizations engaged in educational activities. A combination of vari-ous forms of education and forms of training is allowed. The purpose of the presented work is to analyze the state of the problem of home education in pedagogical theory and practice.Materials and research methods. The basis of the study was foreign and domestic scien-tific and methodological literature, reflecting the historical analysis of the development of home education in Russia and abroad, as well as reflecting the modern formation of the essence of the concept of “home education”. When studying these sources on the problem under consideration, methods of theoretical analysis and synthesis, their abstraction and concretization were used.The methodological basis of the study was the historical and integrated approaches as the most important for understanding the essence and content of home education, identifying specif-ic forms of its implementation and common theoretical and methodological provisions for the identified forms.Results. As a result of the study, the historical aspect of the formation of the concept of “homeschooling” was studied and its wording was clarified, the differences between this con-cept and the concepts of “homeschooling”, “family education” and “distance learning” were re-vealed, and the characteristics of types of homeschooling were disclosed.Conclusion. The theoretical analysis carried out and the conclusions of the study on the problem under consideration can be used in scientific and pedagogical activities when consider-ing the organization of homeschooling. The general and distinctive features of the forms of home education are singled out, as well as the theoretical and methodological provisions of any of the forms of home education are presented.